Alternations in Dynamic and Static Functional Connectivity Density in Chronic Smokers - Yang, Zhengui; Wen, Mengmeng; Wei, Yarui; Huang, Huiyu; Zheng, Ruiping; Wang, Weijian; Gao, Xinyu; Zhang, Mengzhe; Cheng, Jingliang; Han, Shaoqiang; Zhang, Yong (Frontiers in Psychiatry, 2022)
Previous studies have implicated abnormal functional coordination in brain regions of smokers. Neuroimaging studies demonstrated alternations in brain connectivity by using resting-state functional connectivity (rsFC) method which arbitrarily choosing specific networks or seed regions as priori selections, which cannot provide a full picture of the FC changes in chronic smokers. The aim of this study was to investigate the whole-brain functional coordination which measured by functional connectivity density (FCD). As the variance of brain activity, dynamic FCD (dFCD) was performed to investigate dynamic changes of whole-brain integration in chronic smokers. In total, 120 chronic smokers and 56 nonsmokers were recruited, static FCD and dFCD were performed to investigate aberrance of whole-brain functional coordination. Shared aberrance in visual areas has been found both in static and dynamic FCD study in chronic smokers. Furthermore, the results exhibited both heavy smokers and light smokers demonstrated decreased dFCD in visual cortex and left precuneus, as well as increased dFCD in right orbitofrontal cortex, left caudate, right putamen and left thalamus compared with nonsmokers. Besides, alternations of dFCD have been found between heavy smokers and light smokers, and the dFCD variations showed significant positive correlation with smoking-related behaviors. The results demonstrated that chronic smokers not only have some initial areas but also have some regions associated with severity of cigarette smoking. Besides, dFCD could provide more subtle variations in chronic smokers, and the combination of static and dynamic FCD may deepen our understanding of the brain alternations in chronic smokers.